Third Cinema Under Pressure: African Film Aesthetics and the Limits of Revolutionary Film Theory - Achibi Samuel Dede (Goodwood Publishing, 2026)
Purpose: This study explores how contemporary African cinema challenges the assumptions of Third Cinema, particularly its focus on linear temporality, clear ideology, and a uniform, politically educable audience. African filmmakers, through narrative innovation, ritualized performance, spiritual cosmologies, and non-linear temporalities, show that resistance can be subtle, multifaceted, and not always overt or ideologically prescriptive. Research Methodology: The study employs qualitative analysis, examining contemporary African films and their narrative techniques, ritualized performances, and spiritual themes. It critiques the impact of digital platforms, streaming economies, and global festival circuits on audience reception and political engagement in African cinema. Results: The research finds that African cinema transcends the limitations of Third Cinema by demonstrating that resistance in films emerges from form, rhythm, and interpretive complexity, rather than overt political messaging. It highlights how African cinema challenges colonial and postcolonial representations, particularly through its portrayal of women and ethical, social, and historical engagement. Conclusions: The study concludes that Third Cinema serves as a critical point of departure, not a rigid framework, for understanding African cinema. It shows that revolutionary potential lies in subtlety, multiplicity, and temporal depth, offering a reflective and relational form of resistance. Limitation: The study is limited to contemporary African cinema and may not address earlier works or other global film theories outside Third Cinema. Contributions: This paper contributes to the discourse on African cinema by positioning it as a challenge to revolutionary film theory. It highlights how African cinema negotiates power, circulation, and audience interpretation, reframing resistance for the twenty-first century.